2007
DOI: 10.1080/08958370701490379
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Toxicity of Size-Fractionated Airborne Particulate Matter Obtained from Different Cities in the United States

Abstract: Hundreds of epidemiological studies have shown that exposure to ambient particulate matter (PM) is associated with dose-dependent increases in morbidity and mortality. While early reports focused on PM less than 10 microm (PM10), numerous studies have since shown that the effects can occur with PM stratified into ultrafine (UF), fine (FI), and coarse (CO) size modes despite the fact that these materials differ significantly in both evolution and chemistry. Furthermore the chemical makeup of these different siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 34 publications
3
37
1
Order By: Relevance
“…In a different study, these effects were attributed to the insoluble components of the mixture and are not caused by an endotoxin (Wegesser & Last, 2008). The intratracheal exposures in rats and mice, as well as in vitro studies, suggest that similar effects can be observed for coarse and fine PM in the bioassays of lung cells (Gerlofs-Nijland et al, 2007;Halatek et al, 2011;Gilmour et al, 2007;Jalava et al, 2008;Happo et al, 2010) and that coarse PM can be even more hazardous than fine PM. Again, given that the deposition efficiency and pattern of coarse and fine PM differ largely, the health outcomes in a population can differ at equal mass exposures.…”
Section: Toxicological Studiesmentioning
confidence: 65%
“…In a different study, these effects were attributed to the insoluble components of the mixture and are not caused by an endotoxin (Wegesser & Last, 2008). The intratracheal exposures in rats and mice, as well as in vitro studies, suggest that similar effects can be observed for coarse and fine PM in the bioassays of lung cells (Gerlofs-Nijland et al, 2007;Halatek et al, 2011;Gilmour et al, 2007;Jalava et al, 2008;Happo et al, 2010) and that coarse PM can be even more hazardous than fine PM. Again, given that the deposition efficiency and pattern of coarse and fine PM differ largely, the health outcomes in a population can differ at equal mass exposures.…”
Section: Toxicological Studiesmentioning
confidence: 65%
“…This PM 2.5 was provided by Dr. Terry Gordon's laboratory at the NYU Medical Center, resuspended, and ultrasonicated before use. 35 This fraction was chosen because the size of <2.5 ÎŒm in diameter allows the particles to travel via the airways into the alveoli. The dose chosen was at half the concentration of the dose reported to induce significant airway inflammation using PM 2.5 sampled in New York City, 35 Beijing, 36 and Baltimore.…”
Section: Urban Pm 18mentioning
confidence: 99%
“…35 This fraction was chosen because the size of <2.5 ÎŒm in diameter allows the particles to travel via the airways into the alveoli. The dose chosen was at half the concentration of the dose reported to induce significant airway inflammation using PM 2.5 sampled in New York City, 35 Beijing, 36 and Baltimore. Antigen immunization and exposure to antigen and PM Animals were primed and challenged with antigen as described elsewhere 17,18 and schematically presented in Figure 2A.…”
Section: Urban Pm 18mentioning
confidence: 99%
“…The CMB methodology is referred to an unpublished paper for more details (Duvall et al, 2007). Unfortunately, this manuscript as currently available from its authors (Fall of 2007) is no more explanatory of this CMB application than Gilmour et al…”
mentioning
confidence: 99%